Low Income Housing in Mexico An evaluation of thermal comfort and performance of industrialised housing construction system in a Warm-temperate climate - Becerra Santacruz, Habid (Premio Internacional de Tesis de Investigación sobre Vivienda y Desarrollo Sustentable 2016. La Vivienda Social Innovación y Tecnología, 2015)
The construction of low-income mass housing is one of the most common solutions offered by the Mexican government as a response to social pressures arising from high housing demand since the 1960s. The resulting typology is extremely important as it represents a high percentage of the current housing stock in the country, and includes up to 90% of new houses constructed per year. The ongoing housing crisis has forced developers to adopt more sophisticated ways of building houses; large firms in particular have adopted new construction systems that allow them to build a greater volume of housing through the production of repetitive prototypes and the industrialisation of manufacturing processes. Until the present, the effects of the utilisation of these systems on energy optimisation and other aspects, including thermal comfort, have been disregarded. In this context, there is evidence indicating that a significant number of new housing developments present serious problems relating to thermal comfort that are also reflected in high consumption of energy. This research has been conducted at the centre of the country in a region with a warm-temperate climate. The main aim is to investigate and evaluate the current conditions of mass housing developments constructed with a particular industrialised building system, with regard to thermal comfort and thermal performance. Data for this research was gathered through a field study that involved monitoring of indoor climatic conditions and a thermal comfort survey. The monitoring phase encompassed 12 dwellings with four different orientations (north, east, south, and west), measuring internal temperatures and relative humidity levels at 10-minute intervals over the two distinct seasons of the climate of the area (cool and warm). The field survey recorded thermal sensation votes, preference votes and general thermal acceptability to find the average thermal conditions of the studied housing type, from a total of 440 subjects within the two investigated seasons (203 in the cool season and 237 in the warm season). The findings of this research demonstrate a close alignment with the Adaptive Comfort Standard (ACS) from ASHRAE-55 (2004), leading to the conclusion that this standard is suitable for the warm-temperate regions of Mexico. The results from the thermal performance assessment showed that the houses fall substantially outside the comfort zone 43% of the time during the cool season and 41% during the warm season. Furthermore, occupants expressed a high level of dissatisfaction with internal climatic conditions in the analysed typology. This research provides detailed feedback about the performance of the building envelope system, which provides lessons for future projects, and with further investigation and development may translate into improved guidance for building designers.